A Facilities Management Outsourcing Contract Framework - Baba, Maizan; Mohammed, Abdul Hakim; Alias, Buang (CRES, FKSG, 2006)
The objective of this paper is to review a framework of facilities management outsourcing contract, focusing on the processes of the operational stage. Several outsourcing success characteristics need to be addressed prior to the implementation of outsourcing. The outsourcing success characteristics can be grouped into four main factors: communication strategy; performance and operating standards; compatible culture and structure; and control and monitoring. A fluid communication between users and providers is important to establish a clear understanding of the role to be played by each party. Performance and operating standards are essential to ensure that the services provided are assessed and maintained respectively. It is important for the client and the provider to mutually understand the culture of each other's organisation to enable smooth-flowing collaboration and communication in the undertaking of the outsourcing project. The client's and service provider's organisational structures play an influential role in the outsourcing relationship. Reporting, monitoring and control mechanisms are required to assess provider's performance. The framework of facilities management outsourcing contract framework is divided into five operational aspects namely: service start-up; implementation; on-going service development process; review; and project close. The description of services to be outsourced should be outlined in a comprehensive and clear manner during the service start-up. Implementing the outsourcing project requires various undertakings and a client-provider communication is important throughout the implementation of the outsourcing project. Under the on-going service development process, the client and provider should monitor performance of the outsourcing contract including anticipating changes as an approach to adapt to market changes and transformations of trends. It is imperative that reviews on the success of the outsourcing project to be undertaken. Finally, proper mechanisms should be built into the outsourcing agreement for termination of service of the service provider.